STRATEGI KOMUNIKASI PEMASARAN DALAM MENINGKATKAN BRAND AWARENESS PADA FORTHIS HOUSE - Anna Wardani; Kheyene Molekandella Boer (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Universitas Muhammadiyah Cirebon, 2025)
This study aims to analyze the marketing communication strategies implemented by Forthis house to enhance brand awareness and customer loyalty in Samarinda. A descriptive qualitative approach was employed, with data collected through observation, in-depth interviews, and documentation. The informants included the business owner as the key source and two customers as supporting sources. Data analysis followed the Miles, Huberman, and Saldana model, consisting of data condensation, display, and conclusion drawing. The results reveal that Forthis house’s strategy comprises advertising via billboards and social media (Instagram and Tiktok), sales promotion through free samples and event participation, public relations based on customer feedback, personal selling by cashiers, and direct communication facilitated by social media. The combination of digital and direct interaction proved effective in increasing purchase intention, creating positive customer experiences, and building emotional engagement that leads to loyalty. The study concludes that consistency, creativity, and customer involvement are key elements for the success of Forthis house’s marketing communication strategy. Further research is recommended to explore other digital platforms to expand the effectiveness of similar strategies.